Gender Was Associated with Depression but Not with Gastrointestinal Dysfunction in Patients with Parkinson’s Disease - Qin Xiao-ling; Du Yin-zhen; Liu Xue-kui; Li Xue; Cheng Gang; Li Zai-li; Gao Dian-shuai (Parkinson's Disease)
Objective. To investigate the association between gender and gastrointestinal (GI) dysfunctions, as well as gender and other motor symptoms/nonmotor symptoms, in a sample of PD patients. Methods. 186 patients with PD were recruited into this study and divided into male PD group (M-PD) and female PD group (FM-PD). Demographic and PD-related clinical information of the participants were collected by the same neurologist. PD patients were objectively assessed by a spectrum of rating scales of motor symptoms and nonmotor symptoms (including GI dysfunctions). The data were analyzed by SPSS 20 statistical software. Results. Totally 95 cases (51.08%) were in the M-PD group and 91 cases (48.92%) in the FM-PD group. There were no significant differences in age, BMI, and lifestyles between the two groups (P > 0.05). Males had higher educational level (P = 0.002). Females were more likely to have early satiety and loss of appetite (P = 0.025, P = 0.001). There were no significant differences in LED disease duration, age of motor symptoms onset, types of motor symptoms onset, location of motor symptoms onset, and phenotype of motor symptoms between the two groups (P > 0.05). Females had significantly higher UPDRS-III and HAMD scores than males (P = 0.037, P = 0.034). There were no significant differences in PQSI, ESS, RLS, RBD, HAMA, HAMD, and MoCA scores between the two groups. Gender was associated with HAMD (OR = 0.682, P = 0.019). Conclusions. Gender is a risk factor for depression, but not for GI dysfunctions in patients with PD.